Too many PhDs? An invalid argument for countries developing their scientific and academic systems: the case of Portugal - Santos, J. M. (2017)
This article contradicts recent arguments in Portugal that there are “too many PhDs” and argues that there is a need to understand better the changing nature of doctorates and doctorate holders. The article analyzes whether there is a surplus of doctorate holders in Portugal based on five critical dimensions, using data provided by supra-national and national public organizations: stocks and flows; university academic staff qualifications; age structure; research output; and labor market for PhDs. The analysis shows that rather than a surplus, there is a shortage of doctorate holders in many sectors of activity, which is expected to be exacerbated in the next few decades. These findings underline the need to consider active public policies to attract and retain PhDs, as well as enhancing the degree of involvement of new doctorate holders in the modernization of higher education and in the internationalization of the economy. Intermediary institutions, public–private research partnerships and public administration may play a critical role in the process but require new economic actors and instruments with the capacity to invest in and employ doctorate holders.